Oxygen vacancy induced high specific capacitance in Sr2CoSbO6. (September 2022) - Ramesh, Manickam; Viswanath N, Vyshakh; Yesuraj, J.; Kim, Kibum; Biswas, Krishnendu
Abstract: Sr2 CoSbO6, a double perovskite compound known to have oxide ion vacancies, is not well explored for its electrical properties. In the present article, we study the effect of the aliovalent doping of Na + at Sr site in Sr2 CoSbO6 on their electrochemical performance. The X-ray diffraction (XRD) and Scanning Electron Microscope (SEM) techniques confirm the phase formation and reveal particle-like morphologies for all the samples. The cyclic voltammetry study reveals the specific capacitance increases with increasing Na concentration and a specific capacitance value of 228 F/g is obtained for the maximum dopant composition. Excellent cycling stability of 92% of initial capacitance retention even after 2000 continuous cycles at a high scan rate of 100 mVs -1 in an aqueous 1 M KOH electrolyte solution and a 98% of coulombic efficiency at a current density of 1 A/g is observed. These values suggest that the Na doped Sr2 CoSbO6 can find application as supercapacitors material.